High myopia following unilateral cryocoagulation for threshold retinopathy of prematurity - Omar, Nazri; Lo, Yee Lin; Md. Salleh, Rafidah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Despite the proven benefit of cryotherapy in the management of threshold retinopathy of prematurity (ROP), it was shown leading to ocular adverse effects. A male infant was born at 28 week of gestation with a birth weight of 1200 g. Serial examinations revealed worsening ROP in both eyes until he reached a high risk pre-threshold ROP in his right eye and threshold ROP in his left eye. Cryotherapy was performed for the threshold ROP in the left eye while the right eye was subjected to further observation. Subsequently, ROP in both eyes regressed without cicatrisation. The patient was followed-up over 8 years and refractions showed that the treated eye developed steadily increasing myopia while the untreated eye remained emmetropic. This case demonstrated the detrimental effect of cryotherapy to the treated eye leading to the progressive myopia as the child grew.